2010
DOI: 10.1536/ihj.51.319
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Revascularization in Non-Infarct-Related Artery in Multivessel Disease Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: SummaryThis study compared the prognosis of ST-elevation myocardial infarction (STEMI) in patients with multivessel disease (MVD) with that of single vessel disease (SVD) and investigated the revascularization benefit of noninfarct-related artery (IRA) in MVD patients undergoing primary percutaneous coronary intervention (PCI). Between 2002 and 2009, 1278 patients with STEMI underwent primary PCI. Of these patients, 717 (56.1%) with SVD (only IRA obstruction) were placed in group A, while 561 (43.9%) with MVD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The creatinine level 30,32) , LVEF 7, 12) and multiple vessel disease 33) are three traditional risk factors for predicting an unfavorable clinical outcome after AMI and the present study confirmed that these three traditional risk factors were also significant independent predictors of 30-day MACO in patients with STEMI undergoing primary PCI. In addition to traditional risk factors, many biomarkers have been linked to unfavorable clinical outcomes [10][11][12][13][14] of AMI-induced CHF.…”
Section: Discussionsupporting
confidence: 83%
“…The creatinine level 30,32) , LVEF 7, 12) and multiple vessel disease 33) are three traditional risk factors for predicting an unfavorable clinical outcome after AMI and the present study confirmed that these three traditional risk factors were also significant independent predictors of 30-day MACO in patients with STEMI undergoing primary PCI. In addition to traditional risk factors, many biomarkers have been linked to unfavorable clinical outcomes [10][11][12][13][14] of AMI-induced CHF.…”
Section: Discussionsupporting
confidence: 83%
“…However, multivessel disease in STEMI patients continues to pose a major challenge and has been associated with substantially worse prognosis compared with single-vessel disease [4,6,7]. Earlier clinical practice guidelines recommend that in STEMI patients, only the culprit vessel be initially treated, unless hemodynamic compromise is present [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40–50% of patients with STEMI have at least 1 additional severe stenosis lesion of >50% in the non-culprit vessel [4,5]. Patients with multivessel disease (MVD) have worse clinical outcomes in terms of major adverse cardiovascular events (mortality, reinfarction, and target-vessel revascularization) than patients with single-vessel disease [4,6,7]. One-time, multivessel PCI may contribute to a higher risk of complications such as stent thrombosis [810], inflammatory burden [11], and contrast-induced nephropathy [12] associated with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…12) One observational study showed a higher 30-day mortality and one-year mortality in early-staged PCI (the time of staged PCI within one month after primary PCI) when compared to late-staged PCI (the time of staged PCI more than one month and less than 6 months after primary PCI). 13) To the best of our knowledge, no studies have discussed the timing of staged PCI in different territories of STE-MI.…”
Section: Discussionmentioning
confidence: 99%